Towards Cloud-Based Electronic Health Records in Healthcare Systems: Security, Scalability, and Migration Strategies: A Systematic Literature Review - Musawenkosi Moyo; Belinda Ndlovu (Asosiasi Doktor Sistem Informasi Indonesia, 2026)
Cloud-based Electronic Health Records (EHRs) are being adopted rapidly worldwide, but implementation still encounters recurring obstacles in security assurance, elastic scalability, and migration readiness. Prior reviews often treat these issues separately, leaving limited practical guidance for organizations planning end-to-end deployment. This study synthesizes recent evidence on cloud EHR adoption by examining how security controls, scalability claims, and migration strategies interact in real implementation contexts. A systematic literature review following PRISMA guidelines was conducted across ACM Digital Library, PubMed, IEEE Xplore, and ScienceDirect, covering peer-reviewed studies published from 2021 to 2025. Results show that the literature is technically mature in proposing encryption, access control, auditing, and performance optimization, and frequently reports scalability advantages. In contrast, evidence on complete migration pathways—data mapping, interoperability, validation, cutover planning, and post-migration assurance—remains sparse, with many studies relying on simulations rather than longitudinal deployments. The review also identifies geographic concentration in high-income settings, limiting generalizability to resource-constrained health systems. By integrating security, scalability, and migration readiness within a socio-technical, implementation-oriented perspective, this review provides actionable directions for secure and scalable cloud EHR transitions.